Negative Regulation and Protective Function of Natural Killer Cells in HIV Infection: Two Sides of a Coin - Sun, Yu; Zhou, Jie; Jiang, Yongjun (Frontiers in Immunology, 2022)
Natural killer (NK) cells play an important immunologic role, targeting tumors and virus-infected cells; however, NK cells do not impede the progression of human immunodeficiency virus (HIV) infection. In HIV infection, NK cells exhibit impaired functions and negatively regulate other immune cell responses, although NK cells can kill HIV-infected cells and thereby suppress HIV replication. Considerable recent research has emerged regarding NK cells in the areas of immune checkpoints, negative regulation, antibody-dependent cell-mediated cytotoxicity and HIV reservoirs during HIV infection; however, no overall summary of these factors is available. This review focuses on several important aspects of NK cells in relation to HIV infection, including changes in NK cell count, subpopulations, and immune checkpoints, as well as abnormalities in NK cell functions and NK cell negative regulation. The protective function of NK cells in inhibiting HIV replication to reduce the viral reservoir and approaches for enhancing NK cell functions are also summarized.